Scientific Opinion on the welfare risks related to the farming of sheep for wool, meat and milk production - EFSA Panel on Animal Health and Welfare (AHAW) (EFSA Journal, 2014)
Abstract This scientific opinion is the outcome of a scoping exercise aimed to identify the main welfare consequences and associated risk factors for sheep across, and within, categories of management systems and production types. The exercise included the construction of a risk (conceptual) model, a literature review and an expert knowledge elicitation, involving an online survey and a technical hearing, in order to rank the welfare consequences on the basis of the amount of suffering and prevalence. Sheep farmed for wool, meat and milk production were the target population, focusing on ewes and lambs. Based on the degree of human contact, use of housing, nature of pasture management and provision of supplementary feeding, sheep management systems were characterised as: shepherding, intensive, semi‐intensive, semi‐extensive, extensive, very extensive and mixed. The conceptual model proposed seventeen welfare consequences. In ewes, the importance of the welfare consequences was rated differently in different management systems; however, across all systems, the most important welfare consequences were: thermal stress, lameness and mastitis. Prolonged hunger was rated to be more frequent in extensive and very extensive management systems, and mastitis in ewes reared for milk production. For lambs, there were few differences among management systems with thermal stress, pain due to management procedures, gastro‐enteric disorders and neonatal disorders rated as main welfare consequences. Respiratory disorders were more frequent in intensive management systems. The technical hearing of experts facilitated consensus on the major risk factors for ewes and lambs. Animal‐based measures exist for most welfare consequences in ewes and lambs, but many require further validation. The identified currently available validated ABMs for assessing the main welfare consequences in ewes are: body condition score, locomotion score, udder consistency and somatic cell count in milk; and in lambs: shivering, evidence of painful husbandry procedures and dag score (score of breech soiling).